La recevabilité de l'action d'intérêt public - Verge, Pierre (Les Cahiers de droit, 1983)
Referring to doctrinal categories, the judicial control of public authorities' actions could be achieved not only through « private actions », directly aimed at protecting the plaintiffs own subjective rights, but also through so-called public interest actions. The latter represent attempts by « public-spirited » citizens or groups of persons to affirm the rule of law with respect to situations in which they cannot be deemed to be personally and directly aggrieved. The extent to which the courts are ready to consider such public interest actions depends on how they conceive the prerequisite of having a « sufficient interest » in order to bring an action at law. Is a « subjective » or, on the contrary, an « objective » attitude to be adopted in this regard ? The former attitude leads one to consider the impact of the act complained of upon the plaintiffs own interest ; the latter would reflect a primary concern for the social values sought to be affirmed by the intervention of the court. The present text purports to establish the relative acceptance of these trends in defining the locus standi by the Quebec judiciary. Account is taken of the influence of the Thorson-McNeil approach by the Supreme Court of Canada in matters involving a constitutional feature, and also, from a practical point of view, of the use that could be made of Book Nine of the Code of Civil Procedure on Class Actions.